Nitrogen-rich two-dimensional porous polybenzimidazole network as a durable metal-free electrocatalyst for a cobalt reduction reaction in organic dye-sensitized solar cells. (April 2017) - Bae, Seo-Yoon; Kweon, Do Hyung; Mahmood, Javeed; Kim, Min-Jung; Yu, Soo-Young; Jung, Sun-Min; Shin, Sun-Hee; Ju, Myung Jong; Baek, Jong-Beom
Abstract: Nitrogen-enriched two-dimensional (2D) porous polybenzimidazole (2D-HPBI) network was synthesized from the reaction between 1, 2, 4, 5-tetraaminobenzene (TAB) and benzene-1, 3, 5-tricarboxylic acid (BTA) in polyphosphoric acid (PPA) medium. Interestingly, the remnant terminal groups such as amine and carboxyl groups at the periphery of 2D-HPBI were selectively stripped off by heat-treatment at 470 °C. The resultant heat-treated 2D-HPBI (HT-HPBI) displayed substantially improved electrical conductivity and thus outstanding performance as the counter electrode (CE) for the cobalt reduction reaction (CRR) in dye-sensitized solar cells (DSSCs). The charge-transfer resistance ( R ct =0.51 Ω cm 2 ) at the HT-HPBI-CE/electrolyte interface was even lower than that of Pt-CE (1.09 Ω cm 2 ). More importantly, HT-HPBI-based CE showed near "zero" loss of electrochemical stability (1/ R ct ) even after 1000 potential cycles, while the 1/ R ct of Pt decreased to <10% that of a fresh cell. Graphical abstract: Heat-treated two-dimensional (2D) holey polybenzimidazole (HPBI) network, a nitrogen enriched network polymer, displayed outstanding electrocatalytic performance with almost "zero" loss of electrochemical stability even after 1000 potential CV cycles, while the Pt decreased to <10% that of a fresh cell for the cobalt reduction reaction (CRR) in dye-sensitized solar cells (DSSCs). Highlights: Nitrogen-enriched two-dimensional (2D) porous polybenzimidazole (2D-HPBI) was synthesized. To enrich nitrogen content, the periphery groups of 2D-HPBI were selectively removed by heat-treatment. The heat-treated 2D-HPBI (HT-HPBI) displayed outstanding DSSC performance. HT-HPBI-based CE showed near "zero" loss of electrochemical stability after 1000 potential cycles.